2021
DOI: 10.1038/s41433-021-01632-9
|View full text |Cite
|
Sign up to set email alerts
|

An image-based eyelid lesion management service—evaluation of a pilot

Abstract: BACKGROUND/AIMS: Oculoplastics is a predominantly visual specialty and many of the pathologies can be diagnosed based on external appearance. An image-based eyelid lesion management service was piloted to reduce the number of patients who would require outpatient clinic review. The aim of this study was to determine its accuracy and feasibility, both as a hospital-based and community optometrist-based service. If successful, the service was envisaged to significantly reduce the number of patients that require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The successful upscaling of the virtual clinical capacity for glaucoma patients at Moorfields Eye Hospital now means that all new routinely referred patients (around 5000 per annum) can be seen virtually 67 . In a pilot clinic design, a recent study reported substantial agreement between the diagnosis reached by clinicians reviewing patients with suspected lid lesions face to face than when photographs of the lesion were reviewed by consultants 68 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful upscaling of the virtual clinical capacity for glaucoma patients at Moorfields Eye Hospital now means that all new routinely referred patients (around 5000 per annum) can be seen virtually 67 . In a pilot clinic design, a recent study reported substantial agreement between the diagnosis reached by clinicians reviewing patients with suspected lid lesions face to face than when photographs of the lesion were reviewed by consultants 68 …”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that 40% of patients were discharged without intervention from a clinic assessing eyelid lesions, whereas discharge was recommended in 51.6% for the same set of patients when reviewed virtually. Of note, the virtual reviews were performed by a separate consultant ophthalmologist in the latter study 68 . In relation to the sustainability of these systems, no information about cost was reported and it was unclear from the literature how acceptable these systems were to the stakeholders using them.…”
Section: Resultsmentioning
confidence: 99%
“…Oculoplastic VCs have proved successful, partly due to emphasis on visual recognition [ 2 ]. A comparison of face-to-face consultations (F2FC) with photographs assessed independently showed 100% detection rate for extraocular malignancy [ 3 ]. Previous studies on VC uptake were done during a period when concerns of catching Covid-19 in hospitals ran high, possibly influencing patient and clinician responses [ 2 ].…”
mentioning
confidence: 99%
“…Next, we will conduct VCs for non-emergency new referrals, follow-up for investigation results and after minor procedures. For cases necessitating detailed examination, an asynchronous approach whereby photographs are submitted by patients or community optometrists beforehand could be used [ 3 ]. We did not directly compare outcomes with F2FCs, however other peer-reviewed studies show comparable results [ 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation